2020
DOI: 10.1111/pace.13964
|View full text |Cite
|
Sign up to set email alerts
|

Supraventricular tachyarrhythmias during the intrauterine, neonatal, and infant period: A 10‐year population‐based study

Abstract: BackgroundWe aimed to evaluate the incidence, type, and management of supraventricular tachyarrhythmias (SVT) during the first year of life in a retrospective, population‐based, single‐center study during a 10‐year period.MethodsThe analyzed patient cohort is based on data from the only specialized center managing all cases of neonatal and infant SVTs between 2009 and 2018 in the Slovak Republic (5.5 million population). A total of 116 consecutive patients <366 days old were included in the study.ResultsCal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…In the series of Bjelosevic consisting of 116 cases, AVRT was reported as 70% (49% concealed, 18% WPW, and 3% PJRT), FAT (23%), AF (6%), and congenital JET (1%). [11] Similarly, in our study, the most common arrhythmia types were AVRT (45%) and FAT (27%).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the series of Bjelosevic consisting of 116 cases, AVRT was reported as 70% (49% concealed, 18% WPW, and 3% PJRT), FAT (23%), AF (6%), and congenital JET (1%). [11] Similarly, in our study, the most common arrhythmia types were AVRT (45%) and FAT (27%).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, different authors have suggested that heart failure findings may be associated with a rate of 34-48%. [10,11] In the present study, the incidence of SVT and CHD was 32% and the rate of the left ventricular dysfunction on echocardiography was 25%.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…SVT was the second most common arrhythmia in this cohort, after premature beats. As reported, SVT is the most common arrhythmia in infants, and the incidence of SVT requiring inpatient care ranges from 1:4,500-1:5,000 in the first year of life (14)(15)(16). Persistent SVT can cause heart failure, so it should be identified and treated as soon as possible.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the rate of ASD was lower than in our study. In Bjeloševič et al's study of 116 cases of newborns with SVT, the rate of admission to the hospital on the first day was 28% 11 . In our study, 52% of the patients were admitted to the hospital on the first day of life.…”
Section: Discussionmentioning
confidence: 99%